The Maternal Voice: Exploration of Mothers and Birthing Individuals’ Voices in Patient Safety Event and Feedback Reports - Allan Fong; Christian L. Boxley; Seth Krevat; Emily K. Mutondo; Angela D. Thomas (Women's Health Reports)
Background: There is a growing body of research highlighting that Black women have more adverse maternal health events. Instead of only focusing on severe maternal morbidity and mortality events, patient safety events (PSEs) and feedback reports are data sources that can offer insights into a broader spectrum of maternal safety, including near misses, and unsafe conditions. In this work, we explore the racial differences in the representation of mothers and birthing individuals’ (MBIs) voices in PSE and feedback reports. Materials and Methods: We analyze patient experience themes, dissatisfaction, and disrespect in PSE and patient feedback reports from two large birthing hospitals. We compare racial differences in how the voices of MBIs are represented in these reports. Reports were manually coded for the presence of MBIs’ voices, patient experience themes, dissatisfaction, and disrespect by staff. Results: In total, 866 reports were reviewed, of which 271 had explicit mentions of MBIs’ voices. A statistically significant association (p < 0.001) was observed between patient experience themes and report type, driven by clinical safety event themes in PSE reports. A statistically significant association (p = 0.030) was observed between race and report type in 190 reports explicitly mentioning dissatisfaction. Discussion: Delays with handoff and transfer, pain management, patient staff violence, and procedural harm were proportionally more commonly reported among Black MBIs, supporting prior research in pain management and procedural harm disparities. We also identified themes of positive feedback and good catches by patients, which are key components to patient-centered care and promoting resilience in the care process. Conclusions: PSE reports tended to capture predominantly clinical themes from Black MBIs, while feedback reports captured predominantly administrative themes from White MBIs. Important perspectives of the safety narrative can be missed when only PSE reports or feedback reports are considered.